1989
DOI: 10.1002/j.1460-2075.1989.tb03554.x
|View full text |Cite
|
Sign up to set email alerts
|

A phenylalanine ammonia-lyase gene from parsley: structure, regulation and identification of elicitor and light responsive cis-acting elements.

Abstract: We demonstrate that phenylalanine ammonia‐lyase (PAL) in parsley (Petroselinum crispum) is encoded by a small family of at least four genes. The levels of mRNA from three identified PAL genes increase considerably upon treatment of cultured parsley cells with UV light or fungal elicitor and upon wounding of parsley leaves or roots. In cultured cells these changes were shown to involve transcriptional activation. We present the first primary structure of a plant PAL gene (parsley PAL‐1) and the deduced amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
398
2
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(420 citation statements)
references
References 29 publications
18
398
2
1
Order By: Relevance
“…Similarities in promoter architecture between coordinately expressed pal and 4cl genes have been previously observed (Lois et al, 1989;Logemann et al, 1995) and were confirmed in this analysis.…”
Section: Cmas From Different Cenes Are Structurally Similarsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarities in promoter architecture between coordinately expressed pal and 4cl genes have been previously observed (Lois et al, 1989;Logemann et al, 1995) and were confirmed in this analysis.…”
Section: Cmas From Different Cenes Are Structurally Similarsupporting
confidence: 89%
“…3). A remarkable fact is that five of the identified PheMAG CMAs completely overlap with the UV-light-induced in vivo footprints found in parsley cks, pal, and 4-cl gene promoters (Lois et al, 1989;Schulze-Lefert et al, 1989). The remaining CMA, namely chs-CMA3, is contained within light-responsive regions from both soybean chsl5 and Antirrhinum Chs promoters (Lipphardt et al, 1988;Wingender et al, 1990).…”
Section: Analysis Of Phemag Promotersmentioning
confidence: 89%
“…Under the same conditions, no significant activity was driven by the endospermspecific promoter from barley Itrl gene, which was used as a negative control. Activities of the two Ltp gene constructions found in different tissues, using the Ubl-LUC chimeric fusión as internal control, were similar to each other and essentially reproduced the expression pattern obtained by Northern blot analysis, except that Guiltinan et al 1990;Schindler et al 1992 Lois et al 1989;Cramer et al 1989;Ohl et al 1990;Loake et al 1992;Yu et al 1993); and AP-1, consensus TGACACA (API; Després et al 1995). The alignment was constructed out using the CLUSTAL W programme (Thompson et al 1994), and the SIGNAL SCAN 4.0 programme (Prestridge 1991) was used to search for sequence motifs Líp4.2 was more active than Ltp4.3 in endosperm, and Ltp4.3 was active in roots, while Ltp4.2 was not (Fig.…”
Section: 3supporting
confidence: 62%
“…IB). The first motif is present in promoters of phenylpropanoid biosynthetic genes (Cramer et al 1989;Lois et al 1989;Ohl et al 1990;Loake et al 1992;Yu et al 1993), which have been shown to display elicitor-inducible and lightinducible footprints in vivo (Lois et al 1989). The presence of H-box and G-box motifs in the promoter of these genes has been found to be required for elicitor induction (Loake et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, the significance of these latter data is not known as both of these compounds are known to cause non-specific effects on tobacco cell metabolism that are not directly related to gene transcription. It is possible that the elements similar to those described by Lois et aL (1989) are involved in AoPR1 induction at wound sites and at sites of pathogen invasion, but further work is required to substantiate any functional link. In this context it should be noted that there are no H-box sequences in the promoter of the pathogen-inducible potato IPR homologue, pSTH2 (Matton et aL, 1990), so this sequence motif is not necessarily conserved between all the members of the IPR family.…”
Section: The Aopr1 Promoter Contains Sequence Elements Similar To Thomentioning
confidence: 99%